Responsiveness model of the textile supply chain - a structural equation modelling-based investigation. (9th March 2021) - Raghuram, P.; Saleeshya, P.G.
Responsiveness of the supply chain is a crucial factor in improving the capacity to earn greater profits for individual companies and the supply chain as a whole. The ability to meet customer demands promptly and improving the frequency of financial turnover are the direct consequence of responsiveness of their supply chains. This paper aims to examine the effect of the combination of material flow, information flow, lead time and overall capability on the responsiveness of a textile supply chain. With an online-cum-direct survey of 246 textile industries in South India, followed by exploratory factor analysis, we develop a model of supply chain responsiveness. Then, the developed model is validated through structural equation modelling (SEM) using model fit metrics. A comprehensive model considering the entire supply chain may lead to an improved responsiveness, greater financial turnover and allows suitable measures across the supply chain to become more responsive to the customer.